Optimization of Sapta Pesona (Seven Enchantments) with Waste Management on Tourist Village Development: Case of Cimande Tourist Village - Simanihuruk, Maidar (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
Through the community-based tourist approach, coaching of the Sapta Pesona program is one way to provide knowledge to the community that area they live in is a tourist area. Tourists will visit if the area is safe,orderly, clean, cool, beautiful, friendly and memories. The purpose of this research is to know community public awareness of cleanliness, determine the distribution and volume of waste, the waste management evaluation system that has been carried out, and environmental management at Cimande Tourist Village. The Method of research used is qualitative and quantitative methods in order to obtain more comprehensive, valid, reliable, and objective data. The sample consists of 35 participants of coaching from community of Cimande Village. The factor and regression analysis were used for the data analysis. The results of the study showed that coaching significantly contributed to the community interest in waste management (t = 2.512> t table with a significance of 0.017 (? <0.05). The distribution of the generated waste accumulates in almost every RT (neighborhood) and there are 20 illegal landfill garbage dumps. The author makes a suggestion, Urban Village Head with Pokdarwis, Village Cadres and Youth Organization had to have a program to invite all Cimande community to do environmental cleanliness by mutual cooperation on regularly in order to optimize cleanliness with waste management to achieve Cimande Clean, reach out to people from door to door, making them realize the importance of cleanliness and segregation of waste. Keywords: Sapta Pesona, Seven Enchantments, Waste Management, Tourist Village, Cimande